2022
DOI: 10.3390/agronomy12020490
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Globe Artichoke Plants to Potassium Fertilization Combined with the Foliar Spraying of Seaweed Extract

Abstract: This work investigated the effects of potassium mineral fertilizers, combined with biofertilizers (T1–T4 treatments) and the foliar spraying of seaweed extract (at 1 g/L, 2 g/L, and 3 g/L) on the vegetative growth characters, chemical constituents of foliage, and the yield and quality parameters of globe artichoke. The maximum height, and the fresh and dry weight of the leaves, was recorded in plants that received only soil with added potassium (T1 treatment) and sprayed with seaweed extract at 3 g/L. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
1
9
0
2
Order By: Relevance
“…Increasing rates of potassium and phosphorus fertilizers had positive effect on the inulin content of artichoke heads (Elsharkawy et al,2021). Related results were obtained by (Petropoulos et al, 2022) who indicate that applied 75% of recommended dose K significantly increased the inulin content. The best interaction of inulin content recorded when irrigated artichoke plants with 100% ETc magnetized water plus 50% of recommended NPK in both seasons Table 7.…”
Section: Chemical Components Dry Matter (%)supporting
confidence: 62%
See 3 more Smart Citations
“…Increasing rates of potassium and phosphorus fertilizers had positive effect on the inulin content of artichoke heads (Elsharkawy et al,2021). Related results were obtained by (Petropoulos et al, 2022) who indicate that applied 75% of recommended dose K significantly increased the inulin content. The best interaction of inulin content recorded when irrigated artichoke plants with 100% ETc magnetized water plus 50% of recommended NPK in both seasons Table 7.…”
Section: Chemical Components Dry Matter (%)supporting
confidence: 62%
“…However, in the second season there were no significant differences among the three treatments. Semi related results obtained by Petropoulos et al (2022) who found that soil treatment of 75% recommended potassium fertilizer increased quality measures of globe artichoke plants.…”
Section: Head Quality Of Total Yieldmentioning
confidence: 77%
See 2 more Smart Citations
“…The same findings were reported by Akhtar et al (2003) on peas, who reported that the best values of yield and quality traits were attained when potassium fertilizer was applied at 100 kg K 2 O/ha, but above this rate further application of potassium was ineffective. Moreover, Petropoulos et al (2022) showed that using 100 or 75% of the recommended potassium fertilizer dose recorded the best values for yield, quality parameters and chemical compositions of globe artichokes, without significant differences between them. However, Minh et al (2022) showed that the optimum rate of potassium for quinoa grain yield was found to be 105 kg K 2 O/ha which resulted in higher protein and fat contents but lower starch and fiber contents in grains.…”
Section: Introductionmentioning
confidence: 97%